Reviewing the Role of Accountants in Non Governmental Organizations (Ngos): in The Philosophy of The Characteristics of Khulafaur Rasyidin - Putri, Diana; Retnosari, Dyah Silvian; Arisandi, Bustomi (Al-Insyiroh: Jurnal Studi Keislaman, 2024)
This research examines the role of accountants in non-governmental organizations (NGOs) with to study nature and characteristics Caliph Rasyidin . Research This aiming For answer related How role accountant in NGO can reflect nature and characteristics Caliph Rashidun in guard accountability and transparency organization . Research This use library research method with paradigm interpretivism . Library research is conducted with collect and analyze relevant literature​ about role accountant in NGO and nature as well as characteristics Caliph Rasyidin . Paradigm interpretivism used For understand and interpret the data obtained from literature said , with focus on reflection role accountant in context values upheld by the Khulafaur Rasyidin , namely Abu Bakar Ash Shiddiq , Umar bin Khattab, Utsman bin Affan, and Ali bin Abi Thalib . The results of study this expected can give outlook that role accountants are very important , especially in NGO sector which is always sued For behave accountable and transparent . With reflect thoughts and values as held by the companions of the prophets , accountants can help guard accountability and integrity organization . Contribution main from study This is give guide for accountant in NGO for apply values Caliph Rashidun in practice accountancy them , so that can increase trust and credibility organization in the eyes public.